Causal association between non-thyroidal autoimmune diseases and Graves' ophthalmopathy: A mendelian randomization study - Lan Ma; Xue Jiang; Zhijia Hou; Dongmei Li (Advances in Ophthalmology Practice and Research)
Purpose: This Mendelian randomization (MR) analysis study aimed to investigate the genetic causal relationship between non-thyroidal autoimmune diseases (ADs) and Graves' ophthalmopathy (GO). Materials: Single nucleotide polymorphisms (SNPs) associated with inflammatory bowel disease (IBD), multiple sclerosis (MS), psoriasis vulgaris (PV), type 1 diabetes (T1D), systemic lupus erythematosus (SLE), and rheumatoid arthritis (RA) were obtained from the IEU Open genome-wide association studies (GWAS) database, GWAS data for GO were obtained from the FinnGen database. Bidirectional MR analysis was conducted using inverse variance weighted (IVW) method, weighted median (WM) method and MR-Egger test. Cochran's Q statistic was used to assess the heterogeneity between SNP estimates. MR-Egger regression was used to evaluate horizontal pleiotropy and MR pleiotropy residual sum and outlier (MR-PRESSO) test was used to detect the outliers. Results: For non-thyroidal ADs, the forward MR results using the IVM method showed that T1D (OR ​= ​1.259, 95%CI 1.026–1.5465; P ​= ​0.028) and SLE (OR ​= ​1.807, 95%CI 1.229–2.655; P ​= ​0.003) were correlated with the risk of GO at the genetic level, while there was no evidence showing that IBD, MS, PV and RA were correlated with GO. In the reverse MR study, there was a significant increase in the risk of developing T1D in GO (OR ​= ​1.135, 95%CI 1.018–1.265; P ​= ​0.022), but pleiotropy and heterogeneity existed. Conclusions: In the European population, there is strong genetic evidence that patients with T1D and SLE have a higher risk of developing GO, whereas the effect of GO on ADs is unclear.